PENGARUH PENGAWASAN, KOMUNIKASI DAN KOMITMEN ORGANISASI TERHADAP PRESTASI KERJA KARYAWAN PADA PDAM TIRTANADI CABANG PADANG BULAN SUMATERA UTARA - Ritonga, Sinar (UNIKA Santo Thomas, 2020)
The purpose of this research is to examine and analyze the effect of supervison, communication and organizational commitment for employee performance on PDAM Tirtanadi branch Padang Bulan North Sumatera. The data collection was carried out through questionnaires conducted on 43 employees on PDAM Tirtanadi branch Padang Bulan North Sumatera. Data analysis in this study uses SPSS version 22. The sampling technique used is the saturation sampling method and data testing technique used in this study includes the validity test and reliability test. Multiple linear regression analysis and hypothesis testing is also conducted to test and to prove the hypothesis in research. Partial tes results (t test) showed t count (1,721) > t table (1,682) and the significance level was 0,043 < 0,05 proved that supervision had a positive and significant effect on work performance, t count (5,578) > t table (1,682) and the level of significance was 0,000 < 0,05 proved that communication had a positive significant effect on work performance, t count (2,610) > t table (1,682)and the level of significance was 0,013 < 0,05 proved that organizational commitment had a positive and significant effect on achievement work. F test showed that F count > F table was 73,726 > 2,85 and the level of significance (0,000